Induction of the Upstream Regulatory Region of Human Papillomavirus Type 31 by Dexamethasone Is Differentiation Dependent - Bromberg-White, Jennifer L. (American Society for Microbiology, 2003)
Glucocorticoids have been shown to play a role in the transforming abilities of human papillomaviruses (HPVs), and glucocorticoid response elements (GREs) have been identified in the upstream regulatory regions (URRs) of various HPV types. These findings have made glucocorticoids potential therapeutic targets for HPV infection. We have previously shown that the URR of HPV type 31 (HPV31) is insensitive to induction by the synthetic glucocorticoid dexamethasone (dex) in monolayer culture, despite the identification of three potential GREs in the 5′ region of the URR. Due to the fact that the HPV life cycle is intimately linked to the differentiation of the host tissue, we chose to determine whether the URR of HPV31 was inducible by dex under differentiating conditions. Upon suspension of cells in a semisolid medium of methylcellulose, we found that the URR of HPV31 was inducible by dex. The three GREs appear to play roles as independent repressors of this inducibility. By 5′ deletion analysis, the element(s) responsible for this induction was localized to nucleotides (nt) 7238 to 7557. Furthermore, we found that the region between nt 7883 and 7900 appears to act as a repressor of dex inducibility. These findings indicate that epithelial differentiation has a profound effect on the action of dex on the URR of HPV31, suggesting that glucocorticoids play an important role in the differentiation-dependent life cycle of HPV.